An Introduction to the Trinity / [electronic resource] - Marmion, Declan; van Nieuwenhove, Rik (Cambridge : Cambridge University Press, 2010)
Over the last decade there has been a resurgence of writing on the Trinity, indicating a renewal of ideas and debate concerning this key element of Christian theology. This introduction challenges the standard account of a decline and revival in Trinitarian theology, taking into account recent, alternative readings of the theological tradition by Lewis Ayres and Michel Barnes amongst other scholars. By clearly analysing the scope of these new approaches, the authors establish the importance of a considered understanding of the Trinity, resisting the notion of separating faith and reason and identifying theology's link to spirituality. Their account also eschews the easy stereotypes of Western Christianity's supposedly more Unitarian approach as opposed to the more Trinitarian view of the East. Offering an overview of the main people and themes in Trinitarian theology past and present, this book thus provides an accessible, comprehensive guide for students and scholars alike.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).